Evaluation of SterculiaUrens Gum as Novel Carrier for Oral Colon Targeted Drug Delivery System - Nath, Bipul; Kanta Nath, Lila (Journal of Advanced Pharmaceutical Science And Technology, 2013)
The purpose of the research is to evaluate Sterculiaurens gum as a carrier for oral colon targeted drug delivery system. Sterculia gum has been reported to have wide pharmaceutical applications such as tablet binder, disintegrant, gelling agent and as a controlled release polymer, but it has not been exploited as colon targeting carrier. For evaluation as a carrier for colonic delivery of drugs characterization of gum was done. Microflora degradation studies of gum were conducted in phosphate buffer solution (PBS) pH 7.4 containing rat caecal content under anaerobic environment. Solubility, swelling index, viscosity and pH of the polymer solution were determined. Different formulation aspects considered were: gum concentration (10–40%), concentration of citric acid (10–30 %) on swelling index and in-vitro drug release. The results of the isothermal stress testing (IST) shows no degradation of samples of model drug, azathioprine, in the drug polymer mixture and the core tablet excipients. DSC and FT-IR study has proved the compatibility of the drug with Sterculia gum and other tablet excipients. Microflora degradation study revealed that Sterculia gum can be used as tablet excipient for drug release in the colonic region by utilizing the action of enterobacteria. Sterculia gum exhibits premature drug release in the upper GIT without enteric coating and may not reach to the colonic region. From the study, Sterculia gum as colon targeting carrier is possible via coating with chitosan/Eudragit mixed blend polymers which would provide acid as well as intestinal resistance; but undergo enzymatic degradation once it reaches the colon.
Keywords: Sterculia gum; swelling index; microflora degradation; azathioprine; colon delivery; Differential scanning calorimetry